The Response of Paraburkholderia terrae Strains to Two Soil Fungi and the Potential Role of Oxalate - Haq, Irshad Ul; Zwahlen, Reto Daniel; Yang, Pu; van Elsas, Jan Dirk (Frontiers in Microbiology, 2018)
Fungal-associated Paraburkholderia terrae strains in soil have been extensively studied, but their sensing strategies to locate fungi in soil have remained largely elusive. In this study, we investigated the behavior of five mycosphere-isolated P. terrae strains [including the type-3 secretion system negative mutant BS001-ΔsctD and the type strain 17804T] with respect to their fungal-sensing strategies. The putative role of oxalic acid as a signaling molecule in the chemotaxis towards soil fungi, as well as a potential carbon source, was assessed. First, all P. terrae strains, including the type strain, were found to sense, and show a chemotactic response towards, the different levels of oxalic acid (0.1, 0.5 and 0.8 %) applied at a distance. The chemotactic responses were faster and stronger at lower concentrations (0.1 %) than at higher ones. We then tested the chemotactic responses of all strains towards exudates of the soil fungi Lyophyllum sp. strain Karsten and Trichoderma asperellum 302 used in different dilutions (undiluted, 1:10, 1:100 diluted), versus the control. All P. terrae strains showed significant directed chemotactic behavior towards the exudate source, with full-strength exudates inciting the strongest responses. In a separate experiment, strain BS001 was shown to be able to grow on oxalate-amended (0.1% and 0.5%) mineral medium M9. Chemical analyses of the fungal secretomes using proton nuclear magnetic resonance (1H NMR), next to high performance liquid chromatography (HPLC), indeed revealed the presence of oxalic acid (next to glycerol, acetic acid, formic acid and fumaric acid) in the supernatants of both fungi. In addition, citric acid was found in the Lyophyllum sp. strain Karsten exudates. Given the fact that, next to oxalic acid, the other compounds also can serve as C and energy sources for P. terrae, the two fungi clearly offer ecological benefits to this bacterium. The oxalic acid released by the two fungi may have primarily acted as a signaling molecule, and, as a “second option”, a carbon source for P. terrae strains like BS001.